Erwinia Rots and Presence of Pathogenic Bacteria in Symptomless Fruits and Vegetables - F. A., Babalola; L. O., Egwari (Covenant Journal of Physical and Life Sciences, 2017)
Spoilage and contamination of fruits and vegetables with pathogenic microorganisms constitute major agricultural and health concerns to both producers and consumers. The role played by Erwinia species in postharvest losses and the health associated risks in consuming fruits and vegetables without prior heat treatment were investigated. Fruits and vegetable samples collected from three municipal markets were cultured for the presence of Erwinia spp. and pathogenic bacteria. Pathogenicity study for Erwinia was carried out to demonstrate species specific predilection for certain crops. Antibiotic susceptibility of the isolated pathogenic bacteria was carried using the disc diffusion method. Erwinia spp. were isolated more from spoilt vegetables (80% -100%) than from spoilt fruits (65%-100%) and showed species preference for particular crop type. Erwinia papayae was isolated from Carica papaya (pawpaw) only, E. amylovora from Malus domestica (apple, 65%) and Persea americana (avocado pear, 100%), while E. carotovora was isolated from the vegetables; Solanum tuberosum (potato, 100%), Solanum lycopersicum (tomato, 90%), and Alium cepa (onion, 80%). Fruits and vegetables with no obvious symptoms of spoilage were contaminated with species of Salmonella, Shigella, Escherichia, Klebsiella, Pseudomonas, Bacillus and Staphylococcus. Multidrug resistance was found in some of the isolates especially to chloramphenicol, ciprofloxacin, erythromycin and tetracycline. Oxacillin resistance was as high as 29% in coagulase negative staphylococci. These findings underscore the importance of good hygiene and environmental sanitation in maintaining the keeping quality of fruits and vegetables postharvest.